Utilization of healthcare services and renewal of health insurance membership: Evidence of adverse selection in Ghana - Stephen Kwasi Opoku Duku; Francis Asenso-Boadi; Edward Nketiah-Amponsah; Daniel Kojo Arhinful (Health Economics Review, 2016)
Background: Utilization of healthcare in Ghana's novel National Health Insurance Scheme (NHIS) has been increasing since inception with associated high claims bill which threatens the scheme's financial sustainability. This paper investigates the presence of adverse selection by assessing the effect of healthcare utilization and frequency of use on NHIS renewal. Method: Routine enrolment and utilization data from 2008 to 2013 in two regions in Ghana was analyzed. Pearson Chi-square test was performed to test if the proportion of insured who utilize healthcare in a particular year and renew membership the following year is significantly different from those who utilize healthcare and drop-out. Logistic regressions were estimated to examine the relationship between healthcare utilization and frequency of use in previous year and NHIS renewal in current year. Results: We found evidence suggestive of the presence of adverse selection in the NHIS. Majority of insured who utilized healthcare renewed their membership whiles most of those who did not utilize healthcare dropped out. The likelihood of renewal was significantly higher for those who utilize healthcare than those who did not and also higher for those who make more health facility visits. Conclusion: The NHIS claims bill is high because high risk individuals who self-select into the scheme makes more health facility visits and creates financial sustainability problems. Policy makers should adopt pragmatic ways of enforcing mandatory enrolment so that low risk individuals remain enrolled; and sustainable ways of increasing revenue whiles ensuring that the societal objectives of the scheme are not compromised.
Keywords: 330; Health Insurance; Healthcare Utilization; Enrolment; Adverse Selection; Ghana